Approach for Diagnostic and Treatment of Achalasia in the Service of Thoracic Surgery in University Tishreen Hospital - رجب سامر (Latakia University Journal -Medical Sciences Series, 2024)
Achalasia is a rare motor disorder of the esophagus and lower esophageal sphincter. The incidence is approximately 1/100,000 per year and the prevalence rate is 10/100,000. Achalasia is quite difficult to establish because the symptoms might be insidious and therefore not many people come to seek medical attention until it deteriorates to final stage of the disease. There are several modalities that can be used as diagnostic tools such as manometry, barium esophagogram, esophagoduodenoscopy, esophageal CT-scan, until the recent one, high-resolution manometry that can classify achalasia into three different types. The treatment options are the pharmacologic intervention, endoscopic treatment, minimal invasive surgery, and radical surgery. Were studied retrospectively 39 patients,32 of whom presented non-advanced stage of the disease (Stage I/II) and 7 with advanced disease (Stage III/IV). All of them had the clinical conditions to be submitted to surgery. Pre-surgical evaluation was done with a questionnaire based on the most predisposing factors in the development of the disease and the surgical indication was based on the stage of the disease.